Streamlining robotic development : cost and time savings through digital twins and simulations : a thesis presented in partial fulfillment of the requirements for the degree of Master of Engineering in Mechatronics, School of Food and Advanced Technology, Massey University, Palmerston North, New Zealand - Martin-Smith, Craig (Massey University, 2024)
This thesis explores the integration of Digital Twins (DTs) and advanced simulations in robotic development, underscored by recent GPU technology advancements that enhance high-fidelity simulations’ viability. The study focuses on autonomous mobile robots and aims to address the limitations of traditional field testing, which includes high costs and substantial environmental impacts. The research utilises DTs—accurate virtual replicas of physical robots—to improve development efficiency, reduce reliance on physical prototypes, and enhance cost-effectiveness. Featuring four detailed case studies — a line painting robot, an indoor camera-based localisation system, a forestry tool carrier, and an inspection robot—this research illustrates the effectiveness of Digital Twins in verifying and refining robot functionalities prior to physical implementation. The case studies reveal significant efficiencies: the line painting robot saw a time reduction of one month and savings of NZD 8, 080; the localisation system achieved a 44% reduction in costs, saving NZD 9, 380; the forestry robot reduced costs by 20.84%, saving NZD 42, 500; and the inspection robot shortened its development timeline by two months, resulting in savings of NZD 19, 280. Overall, the results affirm that DTs and simulations, bolstered by GPU enhancements, can significantly accelerate development timelines and enhance the precision and quality of robotic systems. This thesis substantiates the transformative impact of DTs and simulations in robotic development, highlighting their crucial role in advancing robotic systems capable of operating in diverse and challenging environments.
Copyright holders of any copyrighted images may use the Copyright Take Down Request link below to request their removal.
Keywords: 400711 Simulation, modelling, and programming of mechatronics systems